TINDAK TUTUR DIREKTIF TENAGA KESEHATAN DALAM PELAYANAN MEDIS DI PUSKESMAS KAMPALA KABUPATEN SINJAI: Directive Speech Acts of Health Workers in Medical Services at Puskesmas Kampala Sinjai District - Miftahul Fauzan, Muhammad Faldi; Usman; Baharman (Journal of Applied Linguistics and Literature, 2025)
This study aims to describe the form of directive speech acts used by health workers in medical services at the Kampala Community Health Centre in Sinjai Regency and the function of directive speech acts used by health workers in medical services at the Kampala Community Health Centre in Sinjai Regency. This study is a qualitative study. This research was conducted at the Kampala Community Health Centre in Sinjai Regency. The research design is descriptive-qualitative. The focus of this research is data in the form of utterances in the form of speech acts expressed by health workers in providing medical services to patients. The source of research data is health workers. Data collection techniques were carried out through observation, recording, note-taking, and documentation. The results of the study reveal that the forms of directive speech acts used by health workers are declarative directive speech acts, interrogative directive speech acts, and imperative directive speech acts. The functions of directive speech acts used by health workers are command, question, prohibition, advice, request, and permission. The use of various forms of directive speech acts by healthcare workers is represented so that patients receive treatment and recovery. The use of various functions of directive speech acts by healthcare workers is represented in order to provide information and help patients achieve recovery